2022
DOI: 10.3233/jad-220361
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Alzheimer’s Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching

Abstract: Background: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including Veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer’s disease (AD) risk in a general cohort of older US adults has not been characterized. Objective: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. Methods: Deidentified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 55 publications
6
39
0
Order By: Relevance
“…("WHO Collaborating Centre for Drug Statistics Methodology, ATC classification index with DDDs, 2023" : https://www.whocc.no/atc_ddd_index/) Hypertension (ICD-9: 491.x, 492.x, 496; ICD-10: J41.x, J42, J43.2, J43.8, J43.9, J44.x) is defined as having two or more outpatient/inpatient diagnosis of elevated blood pressure on different days within the same 24-month in follow-up period. (Bukhbinder et al, 2022) Antihypertensive medications (AHMs)…”
Section: Identification Of MCI Adrd and Hypertensionmentioning
confidence: 99%
“…("WHO Collaborating Centre for Drug Statistics Methodology, ATC classification index with DDDs, 2023" : https://www.whocc.no/atc_ddd_index/) Hypertension (ICD-9: 491.x, 492.x, 496; ICD-10: J41.x, J42, J43.2, J43.8, J43.9, J44.x) is defined as having two or more outpatient/inpatient diagnosis of elevated blood pressure on different days within the same 24-month in follow-up period. (Bukhbinder et al, 2022) Antihypertensive medications (AHMs)…”
Section: Identification Of MCI Adrd and Hypertensionmentioning
confidence: 99%
“…Other interventions include underlying-disease management (e.g., hypertension, diabetes, dyslipidemia, depression, and hearing loss), as stated in WHO guidelines [ 408 ]. More studies should assess the relationship between vaccines and AD; it was found that flu vaccines reduce the risk of AD development [ 409 ]. However, the protective mechanisms have not yet been elucidated.…”
Section: Non-pharmacological Treatment Options and Preventive Measuresmentioning
confidence: 99%
“…Elderly who received the seasonal influenza vaccine were 40% less likely to develop Alzheimer’s disease (AD) in the next 4 years than their unvaccinated peers, according to a retrospective study of almost 2 million US adults aged ≥65 years old. 3 The vaccinated and unvaccinated cohorts, which were matched for their AD propensity at baseline, reported a 5.1% and 8.5% incidence of AD, respectively, at follow-up. The mechanism of action for influenza vaccine to affect AD is unknown.…”
Section: Influenza Vaccination Reduces the Risk Of Alzheimer’s Diseasementioning
confidence: 99%